Efeito agudo e follow-up do treinamento muscular inspiratório sobre a voz e a respiração na doença pulmonar obstrutiva crônica: ensaio clínico randomizado - Gracioli, Marcia da Silva Packaeser (2024)
Introduction: Chronic obstructive pulmonary disease (COPD) is characterized by progressive airflow limitation, exacerbations and extrapulmonary manifestations leading to decreased functional capacity and changes in respiratory muscle strength that may impair voice production. Objective: To examine the acute effects and follow-up of low-intensity inspiratory muscle training on vocal scores and airflow limitation in individuals with COPD. Methods: Randomized clinical trial with seventeen subjects randomly divided into two groups: Inspiratory muscle training and simulated inspiratory muscle training for a single intervention. Inclusion criteria: Age between 40 and 80 years, clinically stable, preserved cognitive function, both genders, and signed informed consent. Variables were assessed before and immediately after inspiratory muscle training and 30 days after training. Data were analyzed using Fisher’s Exact Test, Wilcoxon test, T-test for independent and paired samples with a significance level of ≤ 0.05. Results: There were no significant differences between the Inspiratory Muscle Training and Simulated Inspiratory Muscle Training groups at any time point. There was a significant difference between the within-group means: on the Maximum Phonation Time/e/ in Inspiratory Muscle Training (mean difference = 1.1; 95% CI: -1.8 to -0.3; p = 0.013) and on the Vocal Symptoms Scale in Simulated Inspiratory Muscle Training in the immediate post-training period (mean difference = 2.4; 95% CI: 1.8 to 0.8; p = 0.008). Conclusion: Low-intensity inspiratory muscle training in people with COPD showed immediate positive results in maximal phonation time/e/ and Vocal Symptom Scale, but these were not maintained after 30 days.